2004
DOI: 10.1017/s1350482703001117
|View full text |Cite
|
Sign up to set email alerts
|

A study of twentieth‐century extreme rainfall events in the United Kingdom with implications for forecasting

Abstract: Rainfall events in the United Kingdom during the twentieth century have been surveyed and those identified as extreme by the Flood Studies Report (1975)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 9 publications
1
84
0
Order By: Relevance
“…Other rainfall extremes that impact the study area result from warm season severe convective rainfall events that yield intense winds, heavy rainfall and sometimes hail (and include tornadoes). Convective processes tend to account for extreme rainfall events of 2-6-h and shorter duration while synoptic events can dominate rainfall extremes for durations of around 12 h and longer (Hand et al 2004). Combinations of these synoptic and convective rainfall processes tend to bridge the durations and spatial scales between the two.…”
Section: Study Regionmentioning
confidence: 99%
“…Other rainfall extremes that impact the study area result from warm season severe convective rainfall events that yield intense winds, heavy rainfall and sometimes hail (and include tornadoes). Convective processes tend to account for extreme rainfall events of 2-6-h and shorter duration while synoptic events can dominate rainfall extremes for durations of around 12 h and longer (Hand et al 2004). Combinations of these synoptic and convective rainfall processes tend to bridge the durations and spatial scales between the two.…”
Section: Study Regionmentioning
confidence: 99%
“…There are several criteria and arbitrary thresholds to define extreme precipitation events (Higgins et al, 2000;Zhang et al, 2002;Jones, 2000;Peña and Douglas, 2002;Lyon, 2003;Klein and Können, 2003;Burgueño et al, 2004 among others). Here, heavy rainfall is defined based on the duration and the intensity of precipitation (Hand et al, 2004). We chose a minimum period of four consecutive days to associate the extreme events with more persistent systems that can change the wind patterns in low level and within a larger spatial scale.…”
Section: Methodsmentioning
confidence: 99%
“…Intense, damaging convective rainstorms are therefore a rare but hardly unknown feature of the local climate. It is impossible, and possibly meaningless, to Jackson (1974Jackson ( , 1979 Collinge et al (1990) suggested that "… the reading is likely to be in excess of the true value, as a consequence of insplash, though not by much": the Hewenden Reservoir value -with a storm efficiency of 5.3 -was deemed 'not acceptable' in the Flood Studies Report (NERC 1975, p. 33) although both events were listed in a recent Met Office study by Hand et al (2004). attempt to assign accurate return periods to the extreme events of 16 August 2004, but the preliminary report of the Environment Agency into the flooding in Boscastle (Environment Agency 2005) indicated that the heaviest hourly rainfall had a return period of approximately 400 years and the 3 hour fall approximately 1300 years. It should be noted, however, that the return period of the resultant flooding (also assessed as approximately 400 years) bears only a coincidental relation to the return periods of the rainfall which caused it.…”
Section: How Rare An Event Was This Storm?mentioning
confidence: 99%